RANCANG BANGUN SISTEM TELEMETRI UNTUK MONITORING GAS KARBON MONOKSIDA MENGGUNAKAN JARINGAN WIFI - Arifin Budi Putro; Suryono Suryono (Youngster Physics Journal, 2016)
Development of science and technology is growing rapidly, especially in the field of electronics. Many human activities and industrial activities that produce pollutant gases such as CO disturb the environment. It needs a CO gas concentration monitoring tool for controlling the gas in the environment. The tool is made to measure the concentration of CO gas from long distance so that the monitoring can be done safely by using telemetry. The telemetry system is built by using minimum system microcontroller ATmega8535 to convert analog to digital data from the sensor. For the measurement of the CO gas concentration using MQ-7 sensor which utilizes USART as a serial data communication and WiFi as a wireless data transmission. The result of reading ADC value from MQ-7 sensor is converted into concentration value. The data that has been acquired by a computer then stored in a database and transmitted through WiFi network. Testing of the data transmission system is done by sending a number of data from transmitter to receiver. The comparison of data that is sent and received has an error rate of 0%. Data viewer interface is made using HTML and PHP by displaying several variables such as: temperature, humidity and CO gas concentration. Web browser is used to access the database of the transmitter by entering the IP address of the PC on the transmitter. This CO gas measurement tool helps the efficiency of time in the measurement and be safe in monitoring because it is done from long distance.Keywords: Telemetry, MQ-7 sensor, WiFi, CO, database.